SWAT-3PG: Improving forest growth simulation with a process-based forest model in SWAT. (June 2023) - Karki, R.; Qi, J.; Gonzalez-Benecke, C.A.; Zhang, X.; Martin, T.A.; Arnold, J.G.
Abstract: This study developed a new process-based forest module for the Soil and Water Assessment Tool (SWAT), based on the Physiological Process in Predicting Growth (3-PG) model (SWAT-3PG). The new model allows for improved biomass assimilation, partitioning (stem, foliage, root), and losses (root turnover, foliage loss, mortality). Evaluation at field-scale showed that SWAT-3PG can replicate the different forest biomass components for evergreen forests well. Testing for deciduous and mixed forests sites using remote-sensed data showed that the model can simulate leaf area index (LAI), net primary productivity (NPP) and actual evapotranspiration (AET) reasonably well and can be used to constrain SWAT-3PG when lack of field data. Sensitivity analysis of SWAT-3PG showed its potential in evaluating the impacts of management and climate on forested ecosystems. SWAT-3PG can also be of importance to forest managers as it can estimate variables such as plant height, diameter at breast height (DBH), and basal area. Highlights: The process-based 3-PG model was incorporated in SWAT for tree growth simulation. Subroutines for evergreen, deciduous, and mixed forests were developed to capture different forest systems. SWAT-3PG enhances forest simulation with improved biomass assimilation, partitioning, and losses. SWAT-3PG can be useful to better understand climate and management impacts in forest ecosystems.